Pergumulan Spiritualitas dan Regulasi Emosi Elia dalam 1 Raja-Raja 19:3-4 Menurut James Gross - Semua Anugerah Hansela Neolaka; Merry Kristina Rungkat; Yulius Yusak Ranimpi (Sekolah Tinggi Teologi Aletheia, 2025)
This paper examines Elijah's spiritual struggles and emotional regulation using an interdisciplinary hermeneutic approach and literature review. Elijah struggled with fear due to the conflict with Jezebel and the Israelites about the spread of Baal worship (interpersonal struggles). The situation shook Elijah's spirituality and led to his disappointment with God (divine struggles). The pressure on his mind showed intrapersonal struggles, which culminated in a desire to die. Elijah's emotion regulation process can be seen since he chose to flee as a form of situation selection. To relieve emotional pressure, he modifies the situation by resting and sleeping (situation modification). Eating and drinking in response to the angel's gift reflects attentional deployment. Elijah's cognitive change occurred through God's intervention in the form of a divine encounter and reinforcement. This process reached its final stage in response modulation, where Elijah forgot his desire to die and chose to continue his prophetic duties.